2016
DOI: 10.1016/j.biomaterials.2015.11.023
|View full text |Cite
|
Sign up to set email alerts
|

Stem cell-based gene therapy activated using magnetic hyperthermia to enhance the treatment of cancer

Abstract: Stem cell-based gene therapies, wherein stem cells are genetically engineered to express therapeutic molecules, have shown tremendous potential for cancer applications owing to their innate ability to home to tumors. However, traditional stem cell-based gene therapies are hampered by our current inability to control when the therapeutic genes are actually turned on, thereby resulting in detrimental side effects. Here, we report the novel application of magnetic core-shell nanoparticles for the dual purpose of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
57
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
2
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(64 citation statements)
references
References 56 publications
(61 reference statements)
0
57
0
Order By: Relevance
“…They are upregulated by heavy metals and toxic chemicals, and especially by heat stress, thus protecting cells from hyperthermic damage . Small interfering RNA (siRNA) against HSP70 (HSP70‐siRNA) can inhibit HSP70 synthesis and protein levels, thereby lowering the temperature required to kill cancer cells during hyperthermic treatment. That is, the therapeutic efficacy of PTT should be enhanced by HSP70‐siRNA gene silencing …”
Section: Introductionmentioning
confidence: 99%
“…They are upregulated by heavy metals and toxic chemicals, and especially by heat stress, thus protecting cells from hyperthermic damage . Small interfering RNA (siRNA) against HSP70 (HSP70‐siRNA) can inhibit HSP70 synthesis and protein levels, thereby lowering the temperature required to kill cancer cells during hyperthermic treatment. That is, the therapeutic efficacy of PTT should be enhanced by HSP70‐siRNA gene silencing …”
Section: Introductionmentioning
confidence: 99%
“…Lee et al reported a novel application of magnetic core-shell nanoparticles for the dual purpose of delivering and activating a heat-inducible gene vector that encodes TRAIL in adipose-derived mesenchymal stem cells (AD-MSCs) [86]. This group developed a plasmid harboring the heat shock protein 70B' (HSP70B0) promoter.…”
Section: Trail-based Cell Therapymentioning
confidence: 99%
“…We next tested thermal specificity using hypoxia and heavy metal toxicity as two representative non-thermal stresses [38][39][40] . As a benchmark, we compared with the endogenous HSPA6 promoter, which is a highly stress-inducible HSP promoter 41 previously used for thermal control of gene expression [42][43][44][45] . We tested the gene switches by incubating transduced Jurkat T cells with the hypoxia-mimetic agent CoCl2a stabilizer of the hypoxia response's master regulator Hypoxia Inducible Factor-1α (Hif-1α) 46 as well as the heavy metal complex cadmium chloride (CdCl2).…”
Section: Engineering Thermal-specific Gene Switchesmentioning
confidence: 99%